Preparation, Charaterization and Study of Cobalt (II), Nickel (II), Copper (II) and Zinc (II) Complexes of Some Schiff Bases - Zuhoor W. Al-Tuhafy (College of Education for Pure Sciences, 2010)
ABSTRACT Some complexes having the general formula [ML]X2, [MLX2], where (M= Co+2, Ni+2, Cu+2 and Zn+2, L= the ligand) obtained by the condensation of o-hydroxy acetophenone with o-amino phenol, ethyl amine and 1,3-propane diamine and X= chloride ion) where prepared by the reaction of the metal salt with the ligand in ethanolic solution. The complexes have the molar ratio 1:2, 1:1. The complexes were characterized by elemental analysis, molar conductance, infrared and UV. spectral measurements. The studies revealed that the neutral ligands and giving the most expected octahedral and tetrahedral structures for all complexes.